2015
DOI: 10.1186/s12957-014-0422-4
|View full text |Cite
|
Sign up to set email alerts
|

A giant solitary fibrous tumor of the mesentery: a case report and literature review

Abstract: We report on an extremely rare case of a giant solitary fibrous tumor (SFT) of the mesentery in a 65-year-old male who was admitted to our hospital because of lower abdominal pain and abdominal fullness. Computed tomography demonstrated a well-defined solid mass of 25 × 11 cm located in the lower abdomen, which was completely resected during surgery. Histopathologically, this lesion had a heterogeneous cell population, mainly comprising spindle cells with fibrous collagen proliferation, and various other cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…A recent retrospective series demonstrated that 34% of all SFT occur in the abdominopelvic region and that the abdominopelvic cavity is a major primary site for SFT . However, a SFT that arises from the mesentery is unusual, and a SFT from the mesorectum is rarer still—we found only five reports describing such SFT .…”
Section: Discussionmentioning
confidence: 72%
“…A recent retrospective series demonstrated that 34% of all SFT occur in the abdominopelvic region and that the abdominopelvic cavity is a major primary site for SFT . However, a SFT that arises from the mesentery is unusual, and a SFT from the mesorectum is rarer still—we found only five reports describing such SFT .…”
Section: Discussionmentioning
confidence: 72%
“…In this report, we present an exceedingly rare form of SFT arising from the mesentery, with only 15 cases reported in the literature 3 8 9 12–18. Not infrequently, imaging studies will suggest other entities such as GIST, but histopathology with immunohistochemistry remain the basis of diagnosis 16.…”
Section: Discussionmentioning
confidence: 91%
“…1,9 Recently, eleven cases of SFTs in the small bowel mesentery have been reported in the literature. 2,[10][11][12][13][14] However, the presence of SFT within the wall of the small bowel has been reported only on one occasion: in 2013 by Yong-Qiao Liu and Jun-Qiu Yue. 7 They reported the tumor to be incidentally noted in a 26 year old female during cesarean section.…”
Section: Discussionmentioning
confidence: 99%